Thermal optima of gross primary productivity are closely aligned with mean air temperatures across Australian wooded ecosystems. (20th July 2021) - Bennett, Alison C.; Arndt, Stefan K.; Bennett, Lauren T.; Knauer, Jürgen; Beringer, Jason; Griebel, Anne; Hinko‐Najera, Nina; Liddell, Michael J.; Metzen, Daniel; Pendall, Elise; Silberstein, Richard P.; Wardlaw, Timothy J.; et al.
Abstract: Gross primary productivity (GPP) of wooded ecosystems (forests and savannas) is central to the global carbon cycle, comprising 67%–75% of total global terrestrial GPP. Climate change may alter this flux by increasing the frequency of temperatures beyond the thermal optimum of GPP ( T opt ). We examined the relationship between GPP and air temperature (Ta) in 17 wooded ecosystems dominated by a single plant functional type (broadleaf evergreen trees) occurring over a broad climatic gradient encompassing five ecoregions across Australia ranging from tropical in the north to Mediterranean and temperate in the south. We applied a novel boundary‐line analysis to eddy covariance flux observations to (a) derive ecosystem GPP–Ta relationships and T opt (including seasonal analyses for five tropical savannas); (b) quantitatively and qualitatively assess GPP–Ta relationships within and among ecoregions; (c) examine the relationship between T opt and mean daytime air temperature (MDTa) across all ecosystems; and (d) examine how down‐welling short‐wave radiation (Fsd) and vapour pressure deficit (VPD) influence the GPP–Ta relationship. GPP–Ta relationships were convex parabolas with narrow curves in tropical forests, tropical savannas (wet season), and temperate forests, and wider curves in temperate woodlands, Mediterranean woodlands, and tropical savannas (dry season). Ecosystem T opt ranged from 15℃ (temperate forest) to 32℃ (tropical savanna—wet and dry seasons). The shape of GPP–Ta curves was largely determined by daytime Ta range, MDTa, and maximum GPP with the upslope influenced by Fsd and the downslope influenced by VPD. Across all ecosystems, there was a strong positive linear relationship between T opt and MDTa (Adjusted R 2 : 0.81; Slope: 1.08) with T opt exceeding MDTa by >1℃ at all but two sites. We conclude that ecosystem GPP has adjusted to local MDTa within Australian broadleaf evergreen forests and that GPP is buffered against small Ta increases in the majority of these ecosystems. Abstract : Relationships between gross primary productivity (GPP) and air temperature (Ta) in wooded ecosystems are critical to understanding carbon cycles under changing climates. We examined GPP–Ta relationships of 17 Australian wooded ecosystems dominated by broadleaf evergreen trees occurring over a broad climatic gradient. GPP–Ta relationships were convex parabolas in all ecosystems. The thermal optimum of GPP ( T opt ) was linearly related with mean daytime Ta (MDTa), and T opt exceeded MDTa by >1℃ in most ecosystems. We conclude that GPP has adjusted to local MDTa and is buffered in many of these wooded ecosystems against small Ta increases.